Pentingnya Model Manajemen Pendidikan Karakter Berbasis Teams Games Tournament (TGT) Pada Materi Pembelajaran Bola Voli Tingkat MTsN Kota Padang - Nikmatullaili, Nikmatullaili; Wulandari, Diana; Hadiyanto, Hadiyanto; Sulastri, Sulastri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research analyzes the importance of a character management model based on team games tournaments (TGT) in MTSN volleyball learning material at the Padang City level. In this study, it is part of research and development (R&D). This study uses qualitative descriptive analysis techniques that illustrate the importance of the character education management model based on the Teams Games Tournament (TGT) in the Padang City MTsN level volleyball learning material linked to relevant theories. The discussion results show that TGT can help develop character values ​​such as cooperation, discipline, responsibility, and sportsmanship. Apart from that, TGT also helps increase student motivation and participation in learning, improve their social skills, and create a positive and supportive learning environment. In conclusion, the TGT-based character education management model has proven to be relevant and helpful in improving the quality of volleyball learning at the MTsN level in Padang City and forming better student character. Keywords: Character Education Management Model, Team Games Tournament, Volleyball Learning